IMPLEMENTASI LAYANAN INOVASI SAMSAT KELILING DALAM UPAYAMENINGKATKAN PELAYANAN PEMBAYARAN PAJAK KENDARAAN BERMOTOR - Fitriani Fitriani (ADMINISTRASI PUBLIK, 2021)
The research entitled "Implementation of Mobile SAMSAT Innovation Services in an Effort to Improve Motor Vehicle Tax Payment Services". This research was conducted with the aim of Knowing the Quality of Mobile SAMSAT Innovation Services in an Effort to Improve Motor Vehicle Tax Payment Services. This research itself is a qualitative descriptive research. The focus of this research is Tangible, Realibility, Responsivenes, Anssurance, and Empathy.Based on the research results, the Implementation of Mobile SAMSAT Innovation Services in an Effort to Improve Motor Vehicle Tax Payment Services is quite good. Based on Tangible, Realibility, Responsivenes, Anssurance, and Empathy conducted by Samsat employees around the city of Samarinda, it can be seen that it has been carried out optimally. However, there are still jobs that are considered not optimal, such as the lack of inadequate facilities and infrastructure, lack of socialization of services to the community, and awareness of taxpayers in paying taxes.